Cousins and strangers : Spanish immigrants in Buenos Aires, 1850-1930 - Moya, Jose C., 1952- (ACLS Fellows' publications., 1998)
"More than four million Spaniards came to the Western Hemisphere between the mid-nineteenth century and the Great Depression. Unlike that of most other Europeans, their major destination was Argentina, not the United States. Studies of these immigrants--mostly laborers and peasants--have been scarce in comparison with studies of other groups of smaller size and lesser influence. Presenting original research within a broad comparative framework, Jose C. Moya fills a considerable gap in our knowledge of immigration to Argentina, one of the world's primary "settler" societies. Moya moves deftly between micro- and macro-analysis to illuminate the immigration phenomenon. A wealth of primary sources culled from dozens of immigrant associations, national and village archives, and interviews with surviving participants in Argentina and Spain inform his discussion of the origins of Spanish immigration, residence patterns, community formation, labor, and cultural cognitive aspects of the immigration process. In addition, he provides valuable material on other immigrant groups in Argentina and gives a balanced critique of major issues in migration studies."--Publisher's description